2012 IEEE Colloquium on Humanities, Science and Engineering (CHUSER) 2012
DOI: 10.1109/chuser.2012.6504374
|View full text |Cite
|
Sign up to set email alerts
|

Soft skills implementation in construction management program: A comparative study of lecturers and students perspective

Abstract: -This study aimed to identify the soft skill implementation problems in Construction Management Program based on lecturers and students perception. A total of 95 construction management students and 44 construction management lecturers participated in this study. Data were collected using a questionnaire. Among the variable studies were the understanding of terms and definition, soft skills and general attitudes. Result of the study shows that there is a mismatch between students and lecturers perception in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…According to this study, a construction student has some soft skills that could be developed when working with Bono's 6 thinking hats as a manager, increasing his effectiveness on site. Other studies related to this theme were identified [ 14 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to this study, a construction student has some soft skills that could be developed when working with Bono's 6 thinking hats as a manager, increasing his effectiveness on site. Other studies related to this theme were identified [ 14 , 74 ].…”
Section: Resultsmentioning
confidence: 99%